Administração tributária enquanto serviço público: transparência fiscal e participação como propostas de utilização - Mendes, Layane Sousa (2024)
The Tax Administration has the primary duties of collecting taxes and monitoring taxpayers' due compliance with tax obligations. The resources arising from these activities must be used to benefit society, through the financing of public services. However, the services provided by the Tax Administration involve elements related to the concept of public service, such as provision of activities of public interest and adoption of a public law regime. Given this scenario, the rapprochement between State and society has become imperative, since thecitizen must assume the leading role in the Democratic Rule of Law that currently prevails. In this sense, the objective was to explain fiscal transparency and the participation of taxpayers as proposals for using the public service. Firstly, the concept of public service and its adaptation to the concept of Tax Administration were outlined, as well as its interrelationship with Law no 13,460/17. Next, it was discussed the fundamental rights of the taxpayer, the positive implementation of fiscal transparency in the Brazilian legal system and the right to participation. Finally, public policies were listed to implement the fundamental rights to transparency and participation, discussing, in thistopic, the transparency portals and thebenefits arising from the LAI, as well as discussing participation mechanisms in accordance with the position legal obligation assumed by users of public services. As for the methodology,the research is characterized as qualitative in relation to the approach, as it provides an interpretative/reflective reading of the phenomenon. It is also characterized as bibliographic and documentary, regarding the research technique used. In final considerations, it was found that there had been significant developments in the legislative sphere regarding the fundamental rights to transparency and participation. However, the reasons that prevent the realization of such rights are based on several other social problems that affect society.